Acquiring Indonesian for 3-5 Year Olds in the Children Study Group of Wolosoko Village, Wolowaru District, Ende Regency - Yosef Demon; Veronika Genua (Randwick International of Education and Linguistics Science Journal, 2021)
This study aims to objectively find and describe the acquisition of Indonesian for children aged 3-5 years in the Wolosoko Village Children Study Group, Wolowaru District, Ende Regency (abbreviated as WVCSG). This paper elaborates on the acquisition and the factors that influence the acquisition of Indonesian for children aged 3-5 years at the WVCSG. This research uses a qualitative approach. An approach that emphasizes the originality of the data natural, the researcher acts as a key instrument, the data is collected using the technique of engaging, face-to-face, record and documentation. The data were analyzed using an inductive reasoning model. The theoretical basis of this paper uses Psycholinguistic theory. The results of the study prove that phonologically, children aged 3-5 years are not able to pronounce the sounds [r], [ng], [ny], [y] and [k] perfectly, while children aged 5 years are already able to pronounce these two sounds. perfectly. Morphologically, children aged 3-5 years are able to use basic words and rephrases, while children aged 5 years are able to use three word forms (basic words, rephrases and affix words). Syntactically, children aged 3-5 are able to communicate using 2-3 words while children aged 5 years are able to use 2-5 words in communicating.